TOLERANSI BERMAZHAB DI FAKULTAS SYARIAH DAN HUKUM UNIVERSITAS ISLAM (UIN) RADEN FATAH PALEMBANG - Yusnita, Eti; Andriyani, Andriyani (Universitas Islam Negeri Raden Fatah Palembang, 2018)
This research is about Toleransi Bermazhab Di Fakultas Syariah Dan Hukum Universitas Islam (UIN) Raden Fatah Palembang, motivated by the urgency of educational institutions as a starting point to make changes need to be targeted as an agent of change (agents of change) to tolerance. Islamic universities as one model of educational institutions in Indonesia have a great opportunity to contribute to accelerate the planting of values of tolerance. So no matter how simple, steps or stages of a college institution should be appreciated for the easier change and development done.The main problem in this research is about the understanding of the students of Sharia Faculty and Law UIN Raden Fatah Palembang against tolerance bermazhab and implementation of tolerance among schools of students of the Faculty of Sharia and Fatah Law of UIN Radah Palembang. This research belongs to the type of research This research is a field research where the data collected by observing and distributing questionnaires to students of Faculty of Shari'ah and Law of UIN Raden Fatah Palembang. The results of this study indicate that in the educational environment especially in universities, in this case the students of the Faculty of Shari'ah and Law of the State Islamic University (UIN) Raden Fatah palembang, as well as the community environment, also have a lot of diversity, especially with regard to life and activity college student. Students tend to have an understanding of religious values that are influenced by the family environment in various forms of habit and environment of society with cultural background. All of which will certainly be reflected in their daily attitudes and behaviors.